THE THEORETICAL CONSTRUCTION OF INCOME SMOOTHING MEASUREMENT - Alwan Sri Kustono (Journal of Economics, Business, and Accountancy Ventura, 2011)
The income smoothing is a dimension of the accounts manipulation theme that has been at- tracting a great attention in the accounting literature. A goal of manipulation widely as- cribed to managers is the desire to smooth. Reported income, Income smoothing reflects re- ducing the possible income fluctuations so as to make it as stable as possible throughout the ism.  Almost  of  income  smoothing  research  in  Indonesia  used  Eckel’s  index  to  clasify smoother non smoother firms. Empirical evidences have provided support for the existence of an income smoothing behavior. The studies showed inconsistent about factors determining this smoothing. The purpose of the present investigation is twofold. First, we seek to deter- mine if Eckel index is a reliable instrument to measure income smoothing behavior. Second, we pretend to identify the new instrument to measure incidence of income smoothing. Our research sample comprises manufacturing companies listed on the Indonesia Stock Ex- change, over period of 1999-2008. This study confirms Eckel’s index is not reliability instru- ment. The new proposed index quantifies the incidence of income smoothing without depend on n periods. The results imply that researchers should re-examine the conclusion of previ- ous studies, particularly that determinant, factors and effect of income smoothing practices.